2014
DOI: 10.1109/ted.2014.2362524
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance and Conductance for an MOS System in Inversion, with Oxide Capacitance and Minority Carrier Lifetime Extractions

Abstract: Experimental observations for the In 0.53 Ga 0.47 As metal-oxide-semiconductor (MOS) system in inversion indicate that the measured capacitance (C) and conductance (G or G m ), are uniquely related through two functions of the alternating current angular frequency (ω). The peak value of the first function (G/ω) is equal to the peak value of the second function (−dC/dlog e (ω) ≡ −ωdC/dω). Moreover, these peak values occur at the same angular frequency (ω m ), that is, the transition frequency. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…These doping series samples can also be utilized with regard to the C ox extraction method we 157 published recently, 12 where it was demonstrated that in strong inversion the maximum value of 158 G/at  m is equal to C ox 2 /2(C ox +C D ). In the current study the oxide thickness is fixed while the 159 doping concentration is varied.…”
mentioning
confidence: 99%
“…These doping series samples can also be utilized with regard to the C ox extraction method we 157 published recently, 12 where it was demonstrated that in strong inversion the maximum value of 158 G/at  m is equal to C ox 2 /2(C ox +C D ). In the current study the oxide thickness is fixed while the 159 doping concentration is varied.…”
mentioning
confidence: 99%
“…3 plots the frequency scaled conductance, G/x, and the derivative of capacitance with frequency, ÀxdC/dx, in strong inversion for the post-FGA n-type samples. In recent work [4] it was shown that in strong inversion a relationship exists between G/x and ÀxdC/dx such that they share the same peak magnitude (occurring at x m ) being equal to C ox 2 /2(C ox + C D ) where C ox is the oxide capacitance and C D is the semiconductor maximum depletion capacitance. For these thickness series samples, C ox is varying but the In 0.53 Ga 0.47 As doping and therefore C D , is fixed.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent work has shown how the frequency scaled conductance, G/x, and the derivative of capacitance with angular frequency, ÀxdC/dx, are related, which can be used to evaluate the oxide capacitance and the minority carrier generation lifetime from the In 0.53 Ga 0.47 As MOS system in inversion [4]. The objective of this work is to extend on the results reported in [2,4] to investigate if surface inversion for the Al 2 O 3 / In 0.53 Ga 0.47 As structure can be realized for a reduced E ot , and to determine how the inversion response of the capacitance and conductance, and associated minority carrier generation lifetime, are influenced by post-metallization forming gas annealing.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the frequency behavior of the inversion response, we define the transition frequency, f t , as the frequency where the measured capacitance is at midway between the low frequency capacitance C LF and the high-frequency capacitance C HF , that is, C = 0.5­( C LF + C HF ). It has been shown in refs and that, in strong inversion (here V = +2 V), the parallel conductance divided by the angular frequency G p /ω = G p /(2π f ) features a local maximum at the transition frequency and, thereby, provides an easy and accurate method to determine f t . Several G p /ω versus f curves taken at +2 V are shown in the inset of Figure .…”
Section: Methodsmentioning
confidence: 97%
“…Please note that the aim of our CV simulations was to provide a deeper understanding of the effects arising from changes in bandgap, doping, τ, and direct vs indirect bandgap, but not to precisely reproduce the experimental curves. With use of the physics based simulations, precise fitting of the CV and GV data might though be done in a future study since it would allow the extraction of minority carrier generation rates, as reported by Monaghan et al 19 As the generation rate is closely related to the density of near mid gap traps this material parameter is of interest for both electronic and photonic application.…”
Section: Device Simulationsmentioning
confidence: 99%